-6+4(x+4)=-2(x-5)

Simple and best practice solution for -6+4(x+4)=-2(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+4(x+4)=-2(x-5) equation:



-6+4(x+4)=-2(x-5)
We move all terms to the left:
-6+4(x+4)-(-2(x-5))=0
We multiply parentheses
4x-(-2(x-5))+16-6=0
We calculate terms in parentheses: -(-2(x-5)), so:
-2(x-5)
We multiply parentheses
-2x+10
Back to the equation:
-(-2x+10)
We add all the numbers together, and all the variables
4x-(-2x+10)+10=0
We get rid of parentheses
4x+2x-10+10=0
We add all the numbers together, and all the variables
6x=0
x=0/6
x=0

See similar equations:

| 0.15(x+1,000)=7,050 | | r−42=43 | | 4/6=y/72 | | y-20=8 | | 8-w,w=2 | | 10z=11z+13 | | 2.4v+10.71=131.382 | | 6x-24-2x+48-4x=-60 | | 1-2p=-15 | | y−20=8 | | .x-12=7 | | 11g+3=21–g | | 10-8f-3f=-11f-15 | | 5.8=7+0.7x | | 3x+5.8=0.1 | | 19=-3x+10 | | 8x=64;x= | | 6.3=x+1.8 | | 2(-6b-1)=-2-12b | | 39=f–10+ 45 | | 13.7p-16.43=19p | | 12/10=x/60 | | 3x-8=16 | | 11+6t=6t+9+2 | | (9)(3x)-1=0 | | 5-2l=-5 | | 34+7l=111 | | 15-d=23 | | 4=v/3-1 | | t-1,t=7 | | -3x+8=-5x-18 | | 3-(x+4)=5x+8 |

Equations solver categories